Appropriate use of antiplatelet medications following transient ischemic attacks and stroke: a 9-year study from the Middle East - Naveed, Hiba; Akhtar, Naveed; Al-Jerdi, Salman; Uy, Ryan Ty; Joseph, Sujatha; Morgan, Deborah; Babu, Blessy; Shanthi, Shobana; Shuaib, Ashfaq (Frontiers in Neurology, 2023)
Background and purpose Guidelines recommend that patients with high-risk TIAs and minor strokes presenting within 1–3 days from onset should be offered dual antiplatelet therapy (DAPT). There are little data on real-world adherence to these recommendations. We evaluated the appropriateness of DAPT use in TIA and stroke patients in a prospective database. Methods The Qatar Stroke Database began the enrollment of patients with TIAs and acute stroke in 2014 and currently has 16,000 patients. For this study, we evaluated the rates of guideline-adherent use of antiplatelet treatment at the time of discharge in patients with TIAs and stroke. TIAs were considered high-risk with an ABCD2 score of 4, and a minor stroke was defined as an NIHSS of 3. Patient demographics, clinical features, risk factors, previous medications, imaging and laboratory investigations, final diagnosis, discharge medications, and discharge and 90-day modified Rankin Scale (mRS) were analyzed. Results After excluding patients with ICH, mimics, and rare secondary causes, 8,082 patients were available for final analysis (TIAs: 1,357 and stroke: 6,725). In high-risk TIAs, 282 of 666 (42.3%) patients were discharged on DAPT. In patients with minor strokes, 1,207 of 3,572 (33.8%) patients were discharged on DAPT. DAPT was inappropriately offered to 238 of 691 (34.4%) low-risk TIAs and 809 of 3,153 (25.7%) non-minor stroke patients. Conclusion This large database of prospectively collected patients with TIAs and stroke shows that, unfortunately, despite several guidelines, a large majority of patients with TIAs and stroke are receiving inappropriate antiplatelet treatment at discharge from the hospital. This requires urgent attention and further investigation.